Developmental considerations of young people with cancer transitioning to adulthood. (15th March 2018) - Kim, B.; Patterson, P.; White, K.
Abstract : The literature concerning the impact of having cancer during adolescence and emerging adulthood has been widely discussed in relation to the unique nature of psychosocial challenges. The current study presents these findings within the context of developmental literature to further our understanding on how their developmental transitioning can be affected by having cancer. Specifically, two developmental milestones considered to be the pre‐requisites for acquiring an adult status were focused on: forming identity and establishing independence. Several traditions of developmental literature were incorporated, including the psychosocial, sociological and psychoanalytical perspectives. The study discusses challenges to these developmental processes and suggests measures to foster young people's normative development.